FFR-guided multivessel stenting reduces urgent revascularization compared with infarct-related artery only stenting in ST-elevation myocardial infarction: A meta-analysis of randomized controlled trials. (1st February 2018) - Gupta, Ankur; Bajaj, Navkaranbir S.; Arora, Pankaj; Arora, Garima; Qamar, Arman; Bhatt, Deepak L.
Abstract: Background: Randomized controlled trials (RCTs) have shown fractional flow reserve-guided (FFR) multivessel stenting to be superior to infarct-related artery (IRA) only stenting in patients with ST-elevation myocardial infarction (STEMI) and multivessel disease. This effect was mainly driven by a reduction in overall repeat revascularization. However, the ability to assess the effect of this strategy on urgent revascularization or reinfarction was underpowered in individual trials. Methods: We searched Pubmed, EMBASE, Cochrane CENTRAL, and Web of Science for RCTs of FFR-guided multivessel stenting versus IRA-only stenting in STEMI with multivessel disease. The outcomes of interest were death, reinfarction, urgent, and non-urgent repeat revascularization. Risk ratios (RR) were pooled using the DerSimonian and Laird random-effects model. Results: After review of 786 citations, 2 RCTs were included. The pooled results demonstrated a significant reduction in the composite of death, reinfarction, or revascularization in the FFR-guided multivessel stenting group versus IRA-only stenting group (RR [95%, Confidence Interval]: 0.49 [0.33–0.72], p  < 0.001). This risk reduction was driven mainly by a reduction in repeat revascularization, both urgent (0.41 [0.24–0.71], p  = 0.002) and non-urgent revascularization (0.31 [0.19–0.50], p  < 0.001). Pooled RR for reinfarction was lower in the FFR-guided strategy, but was not statistically significant (0.71[0.39–1.31], p  = 0.28). Conclusions: This systematic review and meta-analysis suggests that a strategy of FFR-guided multivessel stenting in STEMI patients reduces not only overall repeat revascularization but also urgent revascularization. The effect on reinfarction needs to be evaluated in larger trials.